Mechanisms for the free volume tuning the mechanical properties of metallic glass through ion irradiation. (October 2018) - Qiu, Y.H.; Xu, C.; Fu, E.G.; Wang, P.P.; Du, J.L.; Hu, Z.Y.; Yan, X.Q.; Cao, X.Z.; Wang, Y.G.; Shao, L.
Abstract: The irradiation response of metallic glass Ni50 Nb10 Zr15 Ti15 Pt7.5 Cu2.5 under 3 MeV Au ion irradiation was studied. Significant hardness decrease was observed under low dose irradiation. However, the hardness restores to the level of unirradiated sample under higher dose irradiation. Positron annihilation Doppler broadening results indicate that ion bombardment would destroy the short range order (SRO) in metallic glass and introduce excessive free volume under low dose irradiation. While the formation of local ordered structure would consume the free volume due to enhanced atom mobility under higher dose irradiation. Our results help to understand the mechanism of the irradiation effect in metallic glass, and moderate ion radiation can be an efficient way to improve the mechanical property of metallic glass by introducing free volume in metallic glass. Highlights: Remarkable hardness decrease (∼37%) was observed in metallic glass after ion irradiation. Positron annihilation measurement revealed the free volume content change under ion irradiation qualitatively. The correlation between hardness and free volume content in metallic glass was discussed.